Radionuclide methods in assessing pulmonary perfusion and ventilation in patients with connective tissue dysplasia - Zh. V. Vesnina; Zh. Zh. Anashbaev; A. V. Teteneva; N. G. Krivinogov; I. D. Bespalova; S. I. Sazonova; N. A. Serdyukov; K. V. Potapov (Бюллетень сибирской медицины, 2022)
Aim. To perform a scintigraphic assessment of the bronchopulmonary system and pulmonary microcirculation in patients with connective tissue dysplasia.Materials and methods. The study included 31 male patients of conscription age with connective tissue dysplasia (CTD), diagnosed according to the 2019 clinical guidelines (average age (19.6 ± 2.6 years)), and 25 practically healthy individuals comparable in gender and age, who formed a control group. All patients underwent planar pulmonary ventilation – perfusion scintigraphy with determination of pulmonary alveolar – capillary permeability.Results. In patients with CTD, the apical to basal perfusion gradient (U/LQ) was on average 24% lower than in the control group (p = 0.046), and alveolar – capillary permeability was higher in both lungs, both at minute 10 and at minute 30.Conclusion. Static pulmonary ventilation – perfusion scintigraphy allows to identify functional disorders in patients with CTD at the preclinical stage: a decrease in the perfusion gradient on average by 24% compared with the control group and an increase in alveolar – capillary membrane permeability.